Fungsi Waktu “Sembilan Hari” dalam Kosmologi Orang Boti - Aulia Wihelmina Konay; Ebenhaizer I Nuban Timo; Nelman Asrianus Weny (Anthropos: Jurnal Antropologi Sosial dan Budaya (Journal of Social and Cultural Anthropology), 2021)
The study is intended to describe the function of nine days in the Boti's cosmology of the timorese, because for indigenous people, time is always cosmically understood, therefore time is a cycle, always repeating. In the meantime for modern humans, time is mechanically understood and linear. That is, it has a beginning and an end that cannot be repeated. The research used is a kind of qualitative study, which includes information about the Boti in Timor as one of the traditional community communities that still retain a cosmological view of time. That view is nine days (neon) not seven days, according to modern times even the Atoni who already profess Christianity. The study of the Boti's cosmological views was then analyzed from the "sacred time" perspective according to Mircea Eliade's thinking. The analysis produced the find: modern society needs to learn from the life ethos of the Boti in which time is appreciated as a creator and therefore requires a more in-depth study of the concept of time in the local tradition of cultural wealth.